Living in common and deliberating in common : foundational issues for sustainable human development and human security - Anand, P. B.; Gasper, D. (International journal of social economics, 2007)
This e-book was developed from a workshop program with twenty papers under four headings: 1) Goods, Rights and Well-Being, 2) Security and Insecurity, 3) Public Goods and the Millennium Development Goals, and 4) Governance. All papers had relevance to at least one other of these headings, which contributed to rewarding discussions at the workshop and in the follow-up.